KUALITAS PELAYANAN DALAM PEMBUATAN KARTU KELUARGA DI KECAMATAN MEKARMUKTI KABUPATEN GARUT - Heldi Heldi (Sekolah Tinggi Pariwisata Mataram, 2020)
Quality Service Of Making Family Card In Mekarmukti Of Garut. Problem in this research is Mekarmukti employee which not maximal in serving the community especially in making family card as mandated in the constitutional number 25 of 2009 about public service. There are residents which does not care about the importance of having family card, retardation of employee in making family card, less of facilitation in Mekarmukti make the process of making family card was delayed. Research method which used in this research is descriptive qualitative which used interview, study documentation, and obsevation as the technique of collecting data. Data which used in this research is primary data and secondary data with Mekarmukti goverment such as the chief of village, society which chosen by technique of determination informant purposive sampling as the subject of research. Result of this reseach is: the quality service in Mekarmukti already appropriate to the procedure but the facilities in Mekarmukti is the reason why the service is delayed.